2021
DOI: 10.1007/s12310-021-09419-9
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Representation and Willingness to Seek Help as Moderators Between Peer Victimization and Mental Health Outcomes among Latinx Adolescents

Abstract: Importance of gender and attitudes about violence in the relationship between exposure to interparental violence and the perpetration of teen dating violence. Child Abuse & Neglect, 37(5), 343-352.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…This underscores the need for further research to examine this linkage. The present study also demonstrates the need for continued efforts to reduce bullying perpetration in schools to reduce subsequent perpetration, as well as ameliorate a variety of negative outcomes associated with bullying involvement including substance abuse, depressive symptomatology, and suicidality (Kowalski et al, 2014; Polanin et al, 2021; Robinson et al, 2021). We urge professionals to consider gender norms and biases as avenues to bolster prevention efforts in adolescent violence prevention and health promotion programming.…”
Section: Discussionmentioning
confidence: 70%
“…This underscores the need for further research to examine this linkage. The present study also demonstrates the need for continued efforts to reduce bullying perpetration in schools to reduce subsequent perpetration, as well as ameliorate a variety of negative outcomes associated with bullying involvement including substance abuse, depressive symptomatology, and suicidality (Kowalski et al, 2014; Polanin et al, 2021; Robinson et al, 2021). We urge professionals to consider gender norms and biases as avenues to bolster prevention efforts in adolescent violence prevention and health promotion programming.…”
Section: Discussionmentioning
confidence: 70%
“…Among Latinas, protective factors include high self-esteem, emotional regulation, prosocial friendships, positive peer relationships, and peer sociability (Romero et al, 2013). Additionally, Robinson et al (2021) demonstrated that greater willingness to seek help among Latinx students and higher ethnic representation at school were significantly associated with lower levels of depression.…”
Section: Peer Victimizationmentioning
confidence: 97%
“…Peer victimization, often referred to as bullying, occurs when an individual is the target of physical, verbal, and/or social aggression committed by other peers (Robinson et al, 2021). Forms of peer victimization can include intentional group exclusion, teasing, and physical hostility (Reijntjes et al, 2010).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Peer victimization is the experience of being a target of the aggressive behavior of other children, which can be verbal, physical, and/or relational aggression that tends to be repetitive, intentional, and associated with a power imbalance ( Espelage & Holt, 2001 ; Hawker & Boulton, 2000 ). Both cross-sectional and longitudinal studies indicate that peer victimization is associated with adverse mental health outcomes for boys and girls, including depression, suicidal ideation, and low self-esteem ( Polanin et al, 2021 ; Robinson et al, 2021 ; Wu et al, 2021 ). Peer victimization peaks during early adolescence ( Centers for Disease Control and Prevention, 2019 ).…”
Section: Peer Victimizationmentioning
confidence: 99%